2013
DOI: 10.1007/s12013-013-9624-6
|View full text |Cite
|
Sign up to set email alerts
|

Diggin′ on U(biquitin): A Novel Method for the Identification of Physiological E3 Ubiquitin Ligase Substrates

Abstract: The ubiquitin-proteasome system (UPS) plays a central role in maintaining protein homeostasis, emphasized by a myriad of diseases that are associated with altered UPS function such as cancer, muscle-wasting, and neurodegeneration. Protein ubiquitination plays a central role in both the promotion of proteasomal degradation as well as cellular signaling through regulation of the stability of transcription factors and other signaling molecules. Substrate specificity is a critical regulatory step of ubiquitination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…It was reported that HERP is strongly upregulated both at the mRNA and protein level by homocysteine and other ER stress inducers (Hori et al, 2004;Kokame et al, 2000;Rubel et al, 2013). We firstly confirmed that ER stress inducers such as homocysteine, b-mercaptoethanol, tunicamycin, thapsigargin and dithiothreitol (DTT) but not oxidative ER stress inducers such as H 2 O 2 and Paraquat caused the accumulation of HERP protein in HEK293T, HeLa and HCT116 cells by immunoblotting ( Fig.…”
Section: Herp Is Quickly Degraded By the Ubiquitin-proteasome System supporting
confidence: 63%
See 1 more Smart Citation
“…It was reported that HERP is strongly upregulated both at the mRNA and protein level by homocysteine and other ER stress inducers (Hori et al, 2004;Kokame et al, 2000;Rubel et al, 2013). We firstly confirmed that ER stress inducers such as homocysteine, b-mercaptoethanol, tunicamycin, thapsigargin and dithiothreitol (DTT) but not oxidative ER stress inducers such as H 2 O 2 and Paraquat caused the accumulation of HERP protein in HEK293T, HeLa and HCT116 cells by immunoblotting ( Fig.…”
Section: Herp Is Quickly Degraded By the Ubiquitin-proteasome System supporting
confidence: 63%
“…Interaction between gp78 CUE and the HERP UBL domain is essential for HERP polyubiquitylation Substrate specificity is usually determined by E3 (Pickart, 2001;Rubel et al, 2013). We therefore tested whether there was a physical interaction between gp78 and HERP.…”
Section: E2-e3 (Ube2g2-gp78)-complex-mediated Herp Ubiquitylationmentioning
confidence: 99%
“…This method does not rely on protein overexpression, tag fusion proteins, inhibitors or chemical and genetic manipulations and therefore is ideal for the detection of endogenous ubiquitylated proteins [121,122]. To identify substrates of the MuRF1 E3 ligase, TUBEs coupled with two-dimensional differential in-gel electrophoresis (2D-DIGE) and MS were used to compare cells overexpressing either MuRF1 or GFP [93]. This study identified 20 proteins with differential ubiquitylation following MuRF1 overexpression, 3 of which were previously known substrates and 3 that were validated as novel substrates.…”
Section: Proteomicsmentioning
confidence: 99%
“…TUBES have become a widely used tool in molecular biology to trap ubiquitin-bound substrates and are commercially available. New substrates for the striated muscle-specific RING E3 MuRF1 were identified with the use of TUBES, in combination with two-dimensional differential in gel electrophoresis (2D-DIGE) and matrix assisted laser desorption ionization time of flight (MALDI-TOF) mass spectrometry [98]. This technique centers on the comparative analysis of cells with differential (reduced or enhanced) E3 ligase activity.…”
Section: Co-ip and Affinity Purification Of E3s To Identify Substratesmentioning
confidence: 99%